2010
DOI: 10.1091/mbc.e09-11-0967
|View full text |Cite
|
Sign up to set email alerts
|

Global Up-Regulation of Microtubule Dynamics and Polarity Reversal during Regeneration of an Axon from a Dendrite

Abstract: We look inside neurons in vivo and identify major cytoskeletal rearrangements that allow a dendrite to become a regenerating axon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
171
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(186 citation statements)
references
References 39 publications
15
171
0
Order By: Relevance
“…It would be interesting to extend this observation by studying the effect of other AIS perturbations, because it suggests a massive effect of AIS disassembly on MT dynamics at the whole-cell level. Interestingly, up-regulation of EB proteins caused by ankG depletion is similar to the effect of in vivo axotomy in Drosophila neurons (27), demonstrating the profound consequences of AIS disassembly on neuronal polarity.…”
Section: Discussionmentioning
confidence: 82%
“…It would be interesting to extend this observation by studying the effect of other AIS perturbations, because it suggests a massive effect of AIS disassembly on MT dynamics at the whole-cell level. Interestingly, up-regulation of EB proteins caused by ankG depletion is similar to the effect of in vivo axotomy in Drosophila neurons (27), demonstrating the profound consequences of AIS disassembly on neuronal polarity.…”
Section: Discussionmentioning
confidence: 82%
“…We found previously that the number of growing microtubules is up-regulated in dendrites after axon injury (6). To test whether this change in microtubule dynamics might be related to dendrite stabilization, we compared the timing of these two responses.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, its neighbor, at right, has an elaborate dendrite arbor. a microtubule polymerase (13), and RNAi targeting msps eliminates EB1-GFP comets in neurons (6). We therefore used msps RNAi to perturb the behavior of neuronal microtubule plus ends.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stone et al [7], this suggests that minus-end-out rather than mixed MT polarity orientation may be a signature of the dendritic cytoskeleton. There are also some interesting studies on the ability of Drosophila neurons to regenerate after trauma, such as after complete axon removal (Stone et al [11]). It has been shown that regeneration in this case involves complete MT polarity reversal in one dendrite that is later converted to an axon.…”
mentioning
confidence: 99%